Grandparental Availability for Child Care and Maternal Employment: Pension Reform Evidence from Italy - Massimiliano Bratti; Tommaso Frattini; Francesco Scervini (Institute for the Study of Labor (IZA), 2016)
In this paper, we exploit pension reform-induced changes in retirement eligibility requirements to assess the role of grandparental child care availability in the employment of women who have children under 15. We focus on Italy for two reasons: first, it has low rates of female employment and little formal child care provision, and second, it has undergone several pension reforms in a relatively short time span. Our analysis shows that, among the women studied, those whose own mothers are retirement eligible have a 13 percent higher probability of being employed than those whose mothers are ineligible. The pension eligibility of maternal grandfathers and paternal grandparents, however, has no significant effect on the women's employment probability. We also demonstrate that the eligibility of maternal grandmothers mainly captures the effect of their availability for child care. Hence, pension reforms, by potentially robbing households of an important source of flexible, low-cost child care, could have unintended negative consequences for the employment rates of women with children.
Keywords: J13; J22; 330; grandparental child care; maternal employment; pension reform; retirement